2010
DOI: 10.35196/rfm.2010.4.353
|View full text |Cite
|
Sign up to set email alerts
|

EFECTOS HETERÓTICOS Y APTITUD COMBINATORIA EN POBLACIONES DE CHILE DULCE (Capsicum annuum L.)

Abstract: Se estimó la aptitud combinatoria y la heterosis de siete poblaciones criollas de chile ‘Dulce’ (Capsicum annuum L.) y las cruzas resultantes entre ellas, mediante un diseño dialélico. Las 21 cruzas y sus progenitores se evaluaron en Akil y Acanceh, del Estado de Yucatán, México. La unidad experimental fue un surco de 8.0 m con 21 plantas distanciadas a 0.40 m, con distancia entre surcos de 1.20 m. Los experimentos se establecieron en un diseño bloques completos al azar con tres repeticiones. Se midió: rendimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
2
4
1
Order By: Relevance
“…These results are superior to those reported by López Arcos et al [36], but lower than those reported by López-Gómez et al [37]. The differences observed in some of the evaluated characteristics are attributed to the origin and genetics of the materials, characteristics that could be improved through selection and inbreeding [31], although the tested environment also influences in the phenotypic characteristics observed [30]. The variability in agronomic behavior between genotypes could guide the selection of materials with the best phenotypic characteristics and include them in genetic improvement programs, creating varieties adapted to new agroclimatic conditions or specific environments [3,38], since the previously described C. chinenese characters are generally highly heritable [39,40].…”
Section: Agronomic Parameterscontrasting
confidence: 83%
See 1 more Smart Citation
“…These results are superior to those reported by López Arcos et al [36], but lower than those reported by López-Gómez et al [37]. The differences observed in some of the evaluated characteristics are attributed to the origin and genetics of the materials, characteristics that could be improved through selection and inbreeding [31], although the tested environment also influences in the phenotypic characteristics observed [30]. The variability in agronomic behavior between genotypes could guide the selection of materials with the best phenotypic characteristics and include them in genetic improvement programs, creating varieties adapted to new agroclimatic conditions or specific environments [3,38], since the previously described C. chinenese characters are generally highly heritable [39,40].…”
Section: Agronomic Parameterscontrasting
confidence: 83%
“…It should be noted that the mean yields of the evaluated genotypes coincide with those reported by Loatournerie et al [30] in genotypes evaluated in Conkal, Yucatán in 2009. The number of fruits per plant (Figure 1B) in the HNC-5 and HNC-6 genotypes also stood out, as well as the HNC-3 and HNC-2 genotypes, which are selections of the Jaguar variety, a character that could be improved through selection and hybridization [31].…”
Section: Fruit Yield Componentsmentioning
confidence: 95%
“…Two hybrids (H8 and H10) outperformed all parents in yield. These results agree with those reported by Pech‐May et al (2010), who recommended the use of hybridization as a breeding method in Capsicum to increase yield and the number of fruits per plant.…”
Section: Discussionsupporting
confidence: 92%
“…The significant differences ( p ≤ 0.05) found for each agronomic variable demonstrate the wide variability of the investigated habanero pepper material. Some authors (Martínez‐Martínez et al, 2014; Nandadevi & Hosamani, 2003; Pech‐May et al, 2010) reported all similar values for C. annuum .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation